Effect of aspirin on pi-class of rat kidney glutathione S-transferase activity - Yuniarti, Nunung; Martono, Sudibyo; A.M., Supardjan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
The nonsteroids antiinflammatory compounds like curcumin and its analogues, indomethacine, and sulfasalazin have been reported to have an inhibitory effect on GST activity on an in vitro study. The aim of this research is to find out the effect of aspirin on pi-class of rat kidney GST activity in vitro using ethacrynic acid (EA) as a specific substrate for its GST class.Glutathione activity can be measured by conjugating GSH and EA catalyzed with GST. The product can be measured spectrophotometrically to result in a rate (Î absorption/min). With the same method, aspirin was added as an inhibitor. Decreasing conjugation product indicated that there was an inhibitory activity of aspirin.The aspirin inhibitory activity using EA and CDNB (1-chloro-2,4-dinitrobenzene) as substrates are 9,090% (Extrapolated IC50 6665,03 Î¼M) and 14,087% (Extrapolated IC50 4102,0 Î¼M), respectively. These results have shown that aspirin can not inhibit pi-class of rat kidney cytosolic GST activity using EA and CDNB (1-chloro-2,4-dinitrobenzene) as substrates.Key words: aspirin, GSTP, kidney.